IMPLEMENTASI SENAM IRAMA DALAM MENGOPTIMALKAN ASPEK PERKEMBANGAN MOTORIK KASAR ANAK USIA DINI DI PAUD REZEKI KARTIASA TAHUN PELAJARAN 2023-2024 - Suniza; Eliyah, Sera Yuliantini (Jurnal Komunikasi, 2026)
The aim of this research is to reveal: 1) Planning for rhythmic exercises to improve children's gross motor development at PAUD Rezeki Kartiasa for the 2023-2024 academic year; 2) Implementation of rhythmic gymnastics to improve children's gross motor development at PAUD Rezeki for the 2023- 2024 academic year; 3) Evaluation of rhythmic gymnastics in improving aspects of children's gross motor development at PAUD Rezeki Kartiasa for the 2023-2024 academic year. This research technique uses a qualitative approach with a phenomenological type of research. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation, and data conclusion. The results of the research show that planning rhythmic gymnastics to improve children's gross motor development at PAUD Rezeki for the 2023-2024 school year is by determining the goal of the activity, choosing the form of activity to be carried out, and choosing the tools and supporting media used. The implementation of rhythmic gymnastics to improve children's gross motor development at PAUD Rezeki for the 2023- 2024 academic year is by carrying out activities in the warm-up stage, core stage and cooling down stage. Evaluation of rhythmic exercise in improving children's gross motor development at PAUD Rezeki Kartiasa for the 2023- 2023 academic year is by carrying out non-test evaluations, namely interviews and observation evaluations.